Hepatic structure and function after modified jejunoileal bypass surgery for obesity. Issue 6089 (17th September 1977) - Maxwell, J D; Sanderson, I; Butler, W H; Gazet, J C; Pilkington, T R
Abstract : The most serious adverse effect of standard intestinal bypass for obesity is the high incidence of hepatic dysfunction and death from hepatic failure. We therefore examined the long-term effects of a modified form of jejunoileal bypass (in which a greater continuous length of ileum is retained), on liver function in 120 patients. Substantial weight loss (119-0+/-SD 23-3 kg to 82-3+/-18-8 kg) occurred during the first nine months after surgery, accompanied by a significant rise in serum concentrations of bilirubin, alanine transferase, and alkaline phosphatase, and a significant reduction in albumin concentrations. Biochemical changes were unrelated to weight loss or halothane anaesthesia. After weight stabilisation liver function reverted to normal, and four years after bypass sulphobromophthalein retention and hepatic histology did not differ from those in obese controls. There were two postoperative deaths. Three other patients died during the period of rapid weight loss with severe hepatic steatosis. While transient mild impairment of liver function is common after modified jejunoileal bypass, clinically significant hepatic dysfunction is a rare and unexplained early complication.